Analysis of Hot-Carrier Degradation in 22nm FDSOI Transistors Using RF Small-Signal Characteristics - Dang Khoa Huynh; Quang Huy Le; Pardeep Duhan; Defu Wang; Thomas Kämpfe; Matthias Rudolph (2020 German Microwave Conference (GeMiC), 2020)
The following study discusses the impact of hot-carrier degradation on high frequency performance of the 22nm FDSOI n-channel transistors. A quasi-static small-signal equivalent circuit MOSFET model is used to describe the device behavior. RF characteristics are extracted after stressing device with continuous DC. DC characteristics are also investigated thoroughly before and after stress. It is observed that, the device suffers from both interface damage and oxide defect. Accordingly, this study addresses how severe hot-carrier degradation affects the intrinsic parameters as well as the device performance.